Complementary and Alternative Medicine Used by Adolescents in Premenstrual Syndrome- A Cross-Sectional Study: - Elkoca, Ayse; Yekeler Kahraman, Beliz; Ozcan, Handan; Aydin, Muhammet Ali; Karakas, Sevda (Progress in Nutrition, 2022)
Study Objectives: This study was conducted to determine the treatment methods used by adolescents with premenstrual syndrome. Premenstrual syndrome is a common disorder among women of childbearing age. It influences women’s quality of life and economic and social performance. In addition to the conventional treatments by modern medicine, women frequently prefer complementary and alternative medicine practices to cope with the problem. Methods: Quantitative and descriptive design study and 367 people were icluded in this study. A questionnaire consisting of three parts was used to collect the data. The first part includes sociodemographic characteristics and information about the menstrual cycle, the second part is the “Premenstrual Syndrome Scale”, the third part is the “Complementary and Alternative Medicine Scale (CAMS)”. Results: 43.3% of the participants had a family history of PMS, and 64.9% had regular menstrual cycles. 23.2% consulted a physician for their complaints, 10.9% used medication for their complaints. The most preferred complementary and alternative medicine herbal supplementary was green tea (49.5%), chamomile (32.5%), sage (23.8%), and thyme (18.6%). The most used mind-body practices are prayer (65.5%), exercise (54.4%), and namaz (32.4%). Conclusion: It is concluded that 73% of adolescents diagnosed with premenstrual syndrome used complementary and alternative medicine practices, so it is necessary to investigate their effectiveness.